Los procesos de adaptación a la sociedad escolar y su incidencia en el desarrollo de las funciones básicas lecto- escritoras - Salazar Tovar, Nestor (1999)
1.Aspecto historical cultural population of Toacaso. 2. The early school age. 3. behavioral difficulties. 4. Study of the processes of adaptation to the school society Ilinizas School and Colonel Hector Espinoza.